Improving occupational health and safety discipline for accident prevention through the implementation of the 5-S practice - Tanwir, Siti Saroh; Huda, Ahmad Syaiful; Latif, Abdul; Syafi’i, Ahmad; Aulady, M. Ferdaus Noor (Asian Journal of Toxicology, Environmental, and Occupational Health, 2024)
Work accidents are not just a single event but occur through a series of interrelated causes. The main source of accidents is the existence of unsafe actions that refer to worker behavior and unsafe conditions that refer to the work environment. The approach that can be used to prevent work accidents in the work environment is the implementation of the 5S standard through the Plan Do Check Action (PDCA) methodology. The implementation of 5S is carried out in stages and systematically starting from planning, implementation, checking, and continual improvement of each 5S element. Each of the five stages is important and should be taken seriously and handled separately and sequentially. The initial three stages are operational; the fourth phase preserves the state established in the first three phases; and the fifth phase aids in our efforts to improve things continuously. Improved working conditions and an accident-free workplace can result from a better understanding of the 5S idea and how it relates to the safety management system. This will increase employee satisfaction in industrial organizations.